2010
DOI: 10.1590/s0103-84782010000800014
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia e biometria do ligamento apical do pênis de touros da raça Girolando

Abstract: RESUMO Objetivou-se descrever a morfologia e biometria do ligamento apical do pênis de 32 touros da raça Girolando (Bos taurus indicus X Bos taurus taurus, Linnaeus -1758)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
2
0
3
Order By: Relevance
“…A higher incidence of right lateral (62%) versus ventral (38%) deviation, as observed in this study, was also previously reported for the experimental induction of penile deviation by means of a section of the apical ligament (Eurides et al 1994). However, in others studies it was observed that only sectioning the ligament was ineffective in surgical induction of penile deviation (Rabelo et al 2008, Cardoso et al 2010. The occurrence of fibroplasia after surgery in this case could be related to regeneration and functional recovery of the penile apical ligament.…”
Section: A D E B C Fsupporting
confidence: 87%
See 2 more Smart Citations
“…A higher incidence of right lateral (62%) versus ventral (38%) deviation, as observed in this study, was also previously reported for the experimental induction of penile deviation by means of a section of the apical ligament (Eurides et al 1994). However, in others studies it was observed that only sectioning the ligament was ineffective in surgical induction of penile deviation (Rabelo et al 2008, Cardoso et al 2010. The occurrence of fibroplasia after surgery in this case could be related to regeneration and functional recovery of the penile apical ligament.…”
Section: A D E B C Fsupporting
confidence: 87%
“…The degree of penile deviation was graded as mild, moderate or severe based on Cardoso et al (2010). According to this grading system, the axis deviation was considered mild when the angle ranged between 5 to 20º, moderate between 20 and 40º and severe above 40º, as shown in figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O ligamento apical de bovinos é uma faixa fibrosa longitudinal que se origina na face dorsal da túnica albugínea, distalmente a 7,0cm da flexura sigmoide, e se insere na túnica albugínea, nas proximidades do ápice (Schaller, 1999). Em touros da raça Girolanda apresenta, aproximadamente, largura de 0,7mm e espessura de 1,9mm (Cardoso et al, 2010). Possui a função de sustentar o pênis reto (Hafez, 1995).…”
Section: Introductionunclassified
“…Por sua vez Campos et al (2002), perceberam que existe uma correlação linear positiva entre o tamanho do osso peniano e a coluna vertebral em cãesdomésticos. Cardoso et al (2010), verificaram que existe correlação positiva entre o comprimento e a circunferência do pênis com o comprimento do ligamento apical em bovinos. Sendo assim, os dados da correlação aqui apresentados também foram visualizados em outros animais, subsidiando que existem relações entre diferentes tipos de seguimentos corporais.…”
Section: Discussionunclassified